1979
DOI: 10.1126/science.388619
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Diabetes Mellitus: Reversal and Prevention in the BB/W Rat with Antiserum to Rat Lymphocytes

Abstract: Injections of rabbit antiserum to rat lymphocytes reversed hyperglycemia in 36 percent of spontaneously diabetic rats (Bio Breeding/Worcester) and prevented diabetes in susceptible nondiabetic controls. These findings strengthen the hypothesis that cell-mediated autoimmunity plays a role in the pathogenesis of diabetes in this animal model that mimics many morpholigic and physiologic characteristics of human insulin-dependent diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
95
0
1

Year Published

1983
1983
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(97 citation statements)
references
References 9 publications
1
95
0
1
Order By: Relevance
“…By comparison with the normal mouse, the athymic (nude) mouse either does not become diabetic, or becomes much less severely diabetic, when exposed to the encephalomyocarditis virus [1][2][3] or low dose streptozotocin [4][5][6]. If anti-lymphocyte serum is given to spontaneously diabetic BB/W rats, these animals do not develop diabetes [7]. In patients with Type 1 diabetes, different antibodies against islet cells and/or beta cells have been found [8,9], as have abnormal K cell levels [10], and abnormal suppressor cell activities [11].…”
mentioning
confidence: 99%
“…By comparison with the normal mouse, the athymic (nude) mouse either does not become diabetic, or becomes much less severely diabetic, when exposed to the encephalomyocarditis virus [1][2][3] or low dose streptozotocin [4][5][6]. If anti-lymphocyte serum is given to spontaneously diabetic BB/W rats, these animals do not develop diabetes [7]. In patients with Type 1 diabetes, different antibodies against islet cells and/or beta cells have been found [8,9], as have abnormal K cell levels [10], and abnormal suppressor cell activities [11].…”
mentioning
confidence: 99%
“…In earlier studies, whole-body irradiation of BB rats was reported to cause decreased incidence of diabetes [22]; however, irradiation was not followed in that study by immunologic reconstitution, and the high morbidity and mortality observed in the animals make interpretation of the results difficult. In contrast, Rossini, et al [35] found that total lymphoid irradiation of BB rats at a dose of 1600 rads did not decrease frequency of diabetes.…”
Section: Discussionmentioning
confidence: 93%
“…In our study [6], mixed lymphocyte cultures and ConA stimulation assays performed with lymphocytes from the recipient BB rats demonstrated that they had been immunologically reconstituted. Diabetes in the BB rat can be prevented or reversed by various immunosuppressive procedures, such as administration of antilymphocyte globulin [22], glucocorticoids [23], or cyclosporin [23-251. A series of bone marrow irradiation chimeras were constructed [26,27], using various combinations of normal or BB rat recipients and bone marrow donors, in an attempt to determine the site of the defect(s) leading to diabetes and/or T-cell lymphopoenia in the BB rat. If the defect(s) in BB rats leading to diabetes and/or T-cell lymphopoenia resides in the lymphoid stem cells, then transplanting these stem cells from diabetes-prone animals into irradiated diabetes-resistant (normal) animals should induce diabetes and/or lymphopoenia.…”
mentioning
confidence: 99%
“…In the present study, on the analogy of the report that spontaneous diabetes in the BB rat is suppressed by multiple injections of anti-lymphocyte serum [2] we studied the suppressive effects of anti-thymocyte serum (ATS) and anti-Thy 1, 2 monoclonal antibody prepartion on spontaneous diabetes in NOD mice.…”
mentioning
confidence: 99%
“…Although hyperglycemia and elevated plasma glucose concentration have been reported to return to normal levels after treatment with anti-lymphocyte serum (ALS) in approximately 38,90 of diabetic BB rats [2], ATS treatment after the onset of diabetes failed to exert such a curative effect in five out of six NOD mice. The discrepancy between the findings in the BB rat and the NOD mouse might be due to the difference in the frequency of the treatment (ALS was injected to the rats three times weekly for 30 days).…”
mentioning
confidence: 99%